Analysis Of Factors Affecting The Performance Of Village Government Officials In The Implementation Of Government Tasks Village In Lebong Atas Sub-District Lebong District - Mahendera, Iza; Susena, Karona Cahya; Astuty , Kamelia (Tractare: Jurnal Ekonomi-Manajemen, 2024)
This research aims to determine the effect of compensation and job satisfaction on the performance of employees at the Qudwatunaa Islamic boarding school in South Bengkulu. This research is quantitative research with a survey method. Data collection techniques in this research used observation, interviews and were documented with a sample of 44 people. This research results in Compensation (X1) influencing the performance of the employees of the Qudwatunaa Islamic Boarding School, South Bengkulu (Y). This can be seen in the multiple linear regression test, the b1 value (regression coefficient value X1) is 0.036. Apart from that, the b2 value (regression coefficient value 0.05. Based on the research results, it can be concluded that compensation and job satisfaction influence the performance of the employees of the Qudwatunaa Islamic Boarding School, South Bengkulu based on the results of the F-test, the sign value is 0.000 < 0.05 and the f-count value is 10,345 > 3.22